Biography and social exclusion in Europe : experiences and life journeys / edited by Prue Chamberlayne, Michael Rustin and Tom Wengraf. - Chamberlayne, Prue; Rustin, Michael; Wengraf, Tom (Policy, 2002)
Based on 250 life-story interviews in seven EU countries, this text analyses personal struggles against social exclusion and highlights how they are affected by changing welfare regimes. It emphasises the ethnic, gender, generation and class implications of economic and social deregulation.